GAYA KOMUNIKASI COMIC KOMUNITAS STAND UP INDO PKU PEKANBARU - Oki Muhammad; Nurjanah " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
Since the development of stand-up comedy in Indonesia makes the emergence of a community of lovers of stand up comedy which is divided in various regions in Indonesia, including the city of Pekanbaru. In the city of Pekanbaru own community stand up comedyberdiri in november of 2011, which at its inception consisted of only 9 people. Until now has 31 active members in the community that was named Stand Up Indo this PKU. Performers stand up comedy is usually called the comic. In each appearance, comic-comic usually has its own techniques and style in presenting the material stand-up comedy has. Therefore, this study aims to determine the communication style comic community Stand Up Indo PKU Pekanbaru.This study uses qualitative descriptive study, with the selection of informants using purposive, consisting of one internal chairman, and three members of Stand Up Indo PKU community. Data collection techniques using observation, interviews, and documentation. For the data analysis, refer to the interactive model of Miles and Huberman. And for checking the validity of the data using the extension of participation and triangulation techniques.The results of this study indicate stand up comedy techniques used by comic Stand Up Indo PKU community vary. Among them riffing techniques, act out, rule of three, one-liner and roasting. But among some of these techniques, riffing technique is a technique that is always sung comic-comic Stand Up Indo PKU community at the time of his appearance. Furthermore, the community developed communication styles Stand Up Indo PKU include dramatic or dramatic style style, style of animation or animated style and memorable style or style impression